Parque dos bichos na aldeia Vanuíre em Arco Íris-SP - Faccio, Neide Barrocá [UNESP]; Cipriano, Maria Aparecida Frizarin [UNESP]; Andrade, Gustavo de Jesus [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work is the result of studies and surveys did at the surroundings of the Vanuíre native village, placed in the municipality of Arco Íris, on the countryside of São Paulo State, which supported the development of projetual proposition meaning to foster the importance of the local culture throughout the implementation of a park with statues of animals from the regional fauna.

Este trabalho é um desdobramento dos estudos e análises realizadas nos arredores da Aldeia Vanuíre, situada no Município de Arco Íris, no interior do Estado de São Paulo. Tais estudos subsidiaram o desenvolvimento da proposição projetual do Parque dos Bichos com a pretensão de fomentar a significância da cultura local através da construção de um parque com estátuas de animais da fauna regional.
Keywords: Vanuíre native village; Indigenous culture; Ecologic park; Aldeia Vanuíre; Cultura indígena; Parque ecológico